1999
DOI: 10.1002/(sici)1099-1166(199904)14:4<261::aid-gps894>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Life review of an older adult with memory difficulties

Abstract: The natural life review process involves emotional processing of events from the individual's past. Life review therapy (LRT) addresses issues regarding unresolved conflicts, guilt and resentment which the client has particular difficulty in reviewing independently. People with memory problems may have difficulty mentally manipulating a number of pieces of information at the same time. Since LRT involves recollection of past experiences (events, emotions and relationships) which need to be processed and integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…A similar research in the field of life review therapy has not been yet conducted in Iran; however, at the international level, the results of the present study are consistent with the results obtained by Holland (2011), Weiss (2000), Haight et al [19], and Hirsch and Mouratoglou [20]. In line with the above finding, Haight and Webster [21] reported that among 100 life review therapy cases, only 7% of these cases had negative outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…A similar research in the field of life review therapy has not been yet conducted in Iran; however, at the international level, the results of the present study are consistent with the results obtained by Holland (2011), Weiss (2000), Haight et al [19], and Hirsch and Mouratoglou [20]. In line with the above finding, Haight and Webster [21] reported that among 100 life review therapy cases, only 7% of these cases had negative outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Scores range from 0 to 20 (low to high). The LSIA has been used in a variety of settings, including with community-dwelling older adults (Haight, 1988;Haight, 1992), residents of nursing homes (Chao et al, 2006;Cook, 1998;Haight, Michel, & Hendrix, 1998;Hanaoka & Okamura, 2004;Hirsch & Mouratoglou, 1999), and older adults with terminal illness (LeFavi & Wessels, 2003).…”
Section: Outcome Measure: Life Satisfaction Index Version Amentioning
confidence: 99%
“…However, numerous studies have shown that there are many advantages to coherently structuring one's life story. It not only has a positive influence on mood (Fallot, ), life satisfaction (Cook, ), well‐being (Haight, ), depression (Bohlmeijer, Smith, & Cuijpers, ), and anxiety when facing death (Jones, Lyons, & Cunningham, ), but it also helps to resolve memory problems (Hirsch & Mourtoglou, ). It gives the sensation of being in control of one's life as opposed to the sense of powerlessness felt when facing the loss of reference points and identity linked to the aging process.…”
Section: Discussionmentioning
confidence: 99%